Mechanical properties of cotton fabric reinforced geopolymer composites at 200-1000 °C - Alomayri, Thamer; Vickers, Les; Shaikh, Faiz; Low, It Meng (Springer, 2014)
Geopolymer composites containing woven cotton fabric (0–8.3 wt%) were fabricated using the hand lay-up technique, and were exposed to elevated temperatures of 200 °C, 400 °C, 600 °C, 800 °C and 1000 °C. With an increase in temperature, the geopolymer composites exhibited a reduction in compressive strength, flexural strength and fracture toughness. When heated above 600 °C, the composites exhibited a significant reduction in mechanical properties. They also exhibited brittle behavior due to severe degradation of cotton fibres and the creation of additional porosity in the composites. Microstructural images verified the existence of voids and small channels in the composites due to fibre degradation.